P610 Safety of COVID-19 vaccine in patients with Inflammatory Bowel Disease: preliminary data of a national study (ESCAPE-IBD). (21st January 2022) - Todeschini, A; Macaluso, F S; Contaldo, A; Mannino, M; Orlando, A; Principi, M
Abstract: Background: Vaccination is the most effective method to prevent and control the SARS-CoV-2 infection. Recommendations consider patients with inflammatory bowel disease (IBD), Crohn's disease (CD) and ulcerative colitis (UC), a high-priority population to COVID-19 vaccine administration. There were a lot of concerns about vaccination safety in the setting of biological and immunomodulatory drugs. The purpose of this study was to present data on safety about anti-SARS-CoV-2 vaccination in a cohort of IBD patients. These are preliminary data of an ongoing multicenter study assessing effectiveness and safety of COVID-19 vaccines in patients with IBD treated with immunomodulatory or biological drugs (ESCAPE-IBD) sponsored by the Italian Group for the study of Inflammatory Bowel Disease (IG-IBD - ClinicalTrials.gov Identifier: NCT04769258). Methods: Anti-SARS-CoV-2 vaccine (Pfizer-BioNTech®) in two shots were administrated to 427 IBD patients. Afterwards completed vaccination, telephone or in-person interviews were conducted from February to July 2021 by gastroenterologists from referral center to report local and/or systemic adverse events (AEs) related to vaccination. Data on medical history and treatment was collected from electronic health records. Chi-square test was used to compare categorical variables. Logistic regression was used to assess the relationship between disease-related characteristics and the onset of AEs. Results: 427 patients, 252 CD and 175 UC, were enrolled. All patients received two shots of SARS-CoV-2 vaccine. AEs were more common in females (70% vs 50% male gender; p<0.001). Most of them (75%) were in biological or immunomodulatory therapy. About 58% of patients had at least one side effect, following the first dose (13%), the second (22%) or both doses (23%). Local pain at site of injection (31%), fatigue (19%) and fever (15%) were the three most common AEs. Flares of the underlying IBD were not reported. The vast majority of AE were mild and lasted only a few days. No serious AEs were reported and no patient was hospitalized. Logistic regression analysis revealed that female gender (p<0.001) and younger age (p=0.016) were significantly associated with the occurrence of AEs. Conclusion: The short-term vaccine reactions experienced in this cohort of IBD patients were mostly self-limiting, including local pain at the injection site, fatigue and fever. We found a good safety profile of SARS-CoV-2 vaccination in our cohort.